Economic sustainability of small mining communities: a case study of Kathu - Meggersee, Angelien (University of the Free State, 2021)
With the global fluctuations in commodity prices and increasing costs, most mines go through periods of downscale and eventually close down. The closures lead to various negative socio-economic impacts such as higher unemployment, declining growth and increased poverty levels encountered by affected mining communities. This study explores the roles that mining companies and other key stakeholders should play in the development of local economies in order to bring about economic sustainability. The South African legislative and policy framework are scrutinised for their effectiveness in promoting economic sustainability. In addition, key factors limiting the effective implementation of developmental strategies are also identified. Local economic development is often selected as the desired developmental strategy with the aim to create jobs, improve living standards and overall contribute to the economic sustainability of the mining locality. Kathu town, located in the Northern Cape province in South Africa, was used as a case study. Various outlooks, including legal, economic, and social perspectives on the challenges the town face were obtained through the use of interviews, document analysis and memos. Using constant comparative analysis to analyse the data obtained, themes such as a weak community involvement, lack in trust, poor collaboration, poor municipal capacity and possible legislation and policy flaws emerged. The study showed efforts towards sustainable local economic development. However, these efforts might not be sufficient for economic sustainability post mine-closure. Themes in support of this finding include: first, legislation and policy frameworks are promoting growth and not planning for decline to ensure an economically sustainable town. Second, the level of Kathu town’s dependency on the mining companies remain high and the local government is not fulfilling its roles and responsibilities optimally due to the lack of capacity and funding. Third, community members are not participating or contributing to development, however, the proposal of collaborative planning might address the issue. Last, fluctuations in commodity prices and incapacity will hamper the prospects of future development. Despite the challenges hindering the economic development of Kathu town, the mining company and local municipalities realise and acknowledge the shortcomings in their efforts towards promoting economic sustainability. The study makes recommendations about improving the legislative framework and planning arrangements, and hopes to contribute to the knowledge base from which all key stakeholders will learn.
Dissertation (M.Comm. (Economics))--University of the Free State, 2021
Keywords: Economic sustainability; Local economic development; Small town; Mining; Mine closures; Socio-economic effects; Sustainability; Planning for closure; Development policies; Growth theories